PEMBELAJARAN BAHASA INGGRIS MELALUI CONTENT-BASED INSTRUCTION - -, Suharso (Diksi, 2009)
Content-Based Instruction (CBI) is an approach to English language learning thatcombines subject matter contents with language skills. This approach can be employed toenable learners to master such contents and communicate them to other people. Likekilling two birds with one stone, this approach equips learners with such contents andlanguage skills simultaneously. There are two types of CBI, namely the content-drivenprogram and the language-driven program. The former focuses on the contents of aparticular subject matter as the basis of the learning activity organization, whereas thelatter focuses on the language skills. One statement supporting this approach is that itenhances learners' motivation because the materials are authentic and contextual andlearners need such materials in order to master subject matter contents.Keywords: Content-Based Instruction, content-driven, language-driven